Brain Substrates of Behavioral Programs Associated with Self-Regulation - Tops, Mattie; Boksem, Maarten A.; Luu, Phan; Tucker, Don (Frontiers in Psychology, 2010)
The present paper proposes that four neuromodulator systems underpin highly generalized behavioral sets, but each targets either dorsomedial or ventrolateral cortical systems, where it produces its effects in either a proactive or reactive orientation to the environment. This way systems are discriminated that control reactive approach (dopaminergic), reactive avoidance (cholinergic), proactive behavior (noradrenergic), and withdrawal (serotonergic). This model is compared with models of temperament, affect, personality, and so-called two-system models from psychology. Although the present model converges with previous models that point to a basic scheme underlying temperamental and affective space, at the same time it suggest that specific additional discriminations are necessary to improve descriptive fit to data and solve inconsistencies and confusions. We demonstrate how proactive and reactive actions and controls can be confused, and that this has many potential implications for psychology and neurobiology. We uncover conceptual problems regarding constructs such as effortful control, positive affect, approach-avoidance, extraversion, impulsivity, impulse-control, and goal-directedness of behavior. By delineating those problems, our approach also opens up ways to tackle them.